Vascular neutrophilic inflammation and immunothrombosis distinguish severe COVID‐19 from influenza pneumonia. (20th December 2020) - Nicolai, Leo; Leunig, Alexander; Brambs, Sophia; Kaiser, Rainer; Joppich, Markus; Hoffknecht, Marie‐Louise; Gold, Christoph; Engel, Anouk; Polewka, Vivien; Muenchhoff, Maximilian; Hellmuth, Johannes C.; Ruhle, Adrian; et al.
Abstract: Objective: Infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) can lead to severe pneumonia, but also thrombotic complications and non‐pulmonary organ failure. Recent studies suggest intravascular neutrophil activation and subsequent immune cell–triggered immunothrombosis as a central pathomechanism linking the heterogenous clinical picture of coronavirus disease 2019 (COVID‐19). We sought to study whether immunothrombosis is a pathognomonic factor in COVID‐19 or a general feature of (viral) pneumonia, as well as to better understand its upstream regulation. Approach and results: By comparing histopathological specimens of SARS‐CoV‐2 with influenza‐affected lungs, we show that vascular neutrophil recruitment, NETosis, and subsequent immunothrombosis are typical features of severe COVID‐19, but less prominent in influenza pneumonia. Activated neutrophils were typically found in physical association with monocytes. To explore this further, we combined clinical data of COVID‐19 cases with comprehensive immune cell phenotyping and bronchoalveolar lavage fluid scRNA‐seq data. We show that a HLADR low CD9 low monocyte population expands in severe COVID‐19, which releases neutrophil chemokines in the lungs, and might in turn explain neutrophil expansion and pulmonary recruitment in the late stages of severe COVID‐19. Conclusions: Our data underline an innate immune cell axis causing vascular inflammation and immunothrombosis in severe SARS‐CoV‐2 infection.